Non Destructive Determination of Soursop Firmness and Sweetness With Ultrasonic Method - I Wayan Budiastra; Fila Rodotul Jannah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Firmness and sweetness are parameters that significantly affect the quality of soursop fruit. This study aims to examine the application of the ultrasonic method to determine the quality (firmness and sweetness) of soursop fruitnondestructively. Measurements were carried out using three different ripeness levels of soursop fruit, namely immature, ripe, and overripe. Samples were measured using an ultrasonic wave measurement system with a frequency of 50 kHz and followed by measurements of the physicochemical properties such as firmness and total soluble solid (TSS) of the fruit. The results showed that the ultrasonic wave velocity of soursop fruit at three levels of maturity ranged from 169.03–278.31 m/s, while the attenuation coefficient ranged from 9.11–19.94 dB/m. The firmness values, total soluble solids, and density were 1.37–61.59 N, 5.73-17.93 °Brix, and 1014.77–1630.13 kg/m3. There were significant correlations between ultrasonic parameters, firmness, and TSS. Classifying the level of firmness and sweetness on soursop fruit using linear regression equations based on ultrasonic wave velocity parameters produces two-equation functions with the accuracy of classifying soursop fruit on the three levels of firmness and sweetness, namely 100% and 95%. Thus the ultrasonic wave velocity parameter could be used in classifying soursop fruit based on the level of firmness and sweetness.